Ilmu dalam Sejarah: Menyoal Perjalanan Ilmu dan Filsafat Ilmu - Johan Wahyudhi (Buletin Al-Turas, 2012)
Everything around us is in in the law of creation. We can see the same thing when we read history of science which has dialoguistic relation with the philosophy of science. In the case, human, as an intellectual actor who creates science, roles as the conqueror of every challange taht comes from his own environment and nature. As we know, the ratio and common sense are two main softwares to download so much knowledge from many phenomebas in this universe. As long as the time, human has depended on classical tradition in absorbing wisdomswhich are formed to be science in present and fut